2024
DOI: 10.1021/acsami.4c02614
|View full text |Cite
|
Sign up to set email alerts
|

Gene Transfection Efficiency Improvement with Lipid Conjugated Cationic Carbon Dots

Jiuyan Chen,
Fang Li,
Bowen Zhao
et al.

Abstract: An ideal vehicle with a high transfection efficiency is crucial for gene delivery. In this study, a type of cationic carbon dot (CCD) known as APCDs were first prepared with arginine (Arg) and pentaethylenehexamine (PEHA) as precursors and conjugated with oleic acid (OA) for gene delivery. By tuning the mass ratio of APCDs to OA, APCDs-OA conjugates, namely, APCDs-0.5OA, APCDs-1.0OA, and APCDs-1.5OA were synthesized. All three amphiphilic APCDs-OA conjugates show high affinity to DNA through electrostatic inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…134 As an alternative to polymer-based capping agents, lipids and their derivatives, namely unsaturated fatty acids like oleic acid, have been used as non-viral carriers to enhance gene delivery efficiency. 140 For example, Chen and co-workers derived CDs from arginine and pentaethylenehexamine and subsequently functionalized them with oleic acid for improved gene delivery. They showed that CDs conjugated with oleic acid effectively delivered pDNA into both HEK 293 and U2OS cells.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…134 As an alternative to polymer-based capping agents, lipids and their derivatives, namely unsaturated fatty acids like oleic acid, have been used as non-viral carriers to enhance gene delivery efficiency. 140 For example, Chen and co-workers derived CDs from arginine and pentaethylenehexamine and subsequently functionalized them with oleic acid for improved gene delivery. They showed that CDs conjugated with oleic acid effectively delivered pDNA into both HEK 293 and U2OS cells.…”
Section: Applicationsmentioning
confidence: 99%
“…It was shown that the GFP expression levels mediated by CDs-oleic acid were ten times higher as compared with those achieved with PEI in HEK 293 cells. 140…”
Section: Applicationsmentioning
confidence: 99%